2008
DOI: 10.1111/j.1469-8129.2008.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of Australia in pro‐ and anti‐asylum seeker political discourse

Abstract: Whilst there has been a proliferation of research on the role of nationalism in the exclusion of asylum seekers, less attention has been paid to how nationalism can be mobilised in accounts opposing, rather than supporting, harsh antiasylum seeker regimes. This paper compares the ways in which 'Australia' is constructed and used in parliamentary speeches on asylum seekers by both refugee advocates and those seeking harsher asylum seeker laws in Australia. This dual focus is particularly important as it highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 22 publications
2
107
0
Order By: Relevance
“…As Laclau and Chantal Mouffe (1985) argued, hegemonic struggle occurs to occupy the meaning of this nodal signifier. For example, as cited in Every and Augoustinos (2008), Senator Bob Brown of the Australian Greens, during parliamentary debate over the Tampa Affair, stated:…”
Section: Ideological Fantasy and The Fair Gomentioning
confidence: 97%
“…As Laclau and Chantal Mouffe (1985) argued, hegemonic struggle occurs to occupy the meaning of this nodal signifier. For example, as cited in Every and Augoustinos (2008), Senator Bob Brown of the Australian Greens, during parliamentary debate over the Tampa Affair, stated:…”
Section: Ideological Fantasy and The Fair Gomentioning
confidence: 97%
“…However, there are also practical implications arising from our article. The first is the degree of false beliefs espoused by many participants and the fact that they are reinforced by the media and politicians (see Every & Augoustinos, 2008). In one study, it was found that if you consistently hear something, false or otherwise, you are much more likely to remember it (Skurnik, Yoon, Park, & Schwarz, 2005).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Therefore, where does information that community members hold about asylum seekers originate? We argue that it is likely that such information comes from the media and, in particular, from politicians (Every & Augoustinos, 2008). Yet, not everybody accepts the information that is given to them.…”
Section: Third-person Effectmentioning
confidence: 99%
“…Pride in their advantage as a citizen of Australia is also seen as a legitimate and fair reflection of their worth (see Leach et al 2002). While national identity can be used to argue for inclusion of asylum seekers, as Every and Augoustinos (2008) found, for Do-Badders it had an exclusionary effect.…”
Section: Do-baddersmentioning
confidence: 99%
“…Do-Badders either focused on the rights of Australians over and above those of others; or used a limited definition of humanitarian obligations, focusing on the harmful practice of asylum seeking and the need to protect people from its dangers. On the other hand, Do-Gooders argued for humanitarian approaches on two grounds -one that it is in the national character and good for Australians (see Every & Augoustinos, 2008;Gale, 2004), the other that it is part of our responsibility to other human beings generally.…”
Section: Do-goodersmentioning
confidence: 99%